Nonlinear static analysis of an asymmetric unreinforced masonry building using macro-element modelling approach - Asikoglu, Abide (2019)
Past seismic events showed that irregular structures are subjected to more damage compared to the regular ones. Although seismic codes prohibit or discourage irregularities by imposing certain penalties, the design of these type of structures can be inevitable due to functional and architectural concerns. In fact, structures designed as regular configuration can also present behavior induced by torsional effects due to progressive damage and irregular load distribution after experiencing seismic events. The present paper focuses on the seismic performance of a half-scale two story unreinforced masonry building with asymmetric structural configuration. Structural irregularity both in plan and as openings in elevation was considered. Nonlinear static analyses were performed using macro-element modeling approach in two different software available for masonry structures, namely 3DMacro and TREMURI. Results obtained from the two software were compared in terms of capacity and damage patterns. It was seen a considerable difference in capacity curves. Additionally, several sensitivity analyses were carried out and sensitivity of the model to certain parameters, such as tensile strength, friction coefficient, and shear strength, was assessed.